Fetal cardiovascular magnetic resonance imaging. - Aguet, Julien; Seed, Mike; Marini, Davide (Pediatric Radiology, 2020)
Fetal cardiovascular MRI is showing promise as a clinical diagnostic tool in the setting of congenital heart disease when the cardiac anatomy is unresolved by US or when complementary quantitative data on blood flow, oxygen saturation and hematocrit are required to aid in management. Compared with postnatal cardiovascular MRI, prenatal cardiovascular MRI still has some technical limitations. However, ongoing technical advances continue to improve the robustness and usability of fetal cardiovascular MRI. In this review, we provide an overview of the state of the art of fetal cardiovascular MRI and summarize the current focus of clinical application for this versatile technique.